2008
DOI: 10.1007/s10552-008-9218-6
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of vulvar cancer and vulvar intraepithelial neoplasia in young Australian Indigenous women

Abstract: These data provide evidence of a geographic cluster of vulvar cancer in remote Indigenous communities in northern Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…19 The relatively high incidence of vulva cancer in remote areas is probably not a national issue, but due to an epidemic of this otherwise very rare cancer in young women in Arnhem Land. 20 When the NT was excluded from the analysis, there was no excess of vulva cancer in younger Indigenous women. Improvement in the accuracy of Indigenous status data is required not only in the four low-identification registries, but also in the four high-identification registries to a lesser extent.…”
Section: Discussionmentioning
confidence: 99%
“…19 The relatively high incidence of vulva cancer in remote areas is probably not a national issue, but due to an epidemic of this otherwise very rare cancer in young women in Arnhem Land. 20 When the NT was excluded from the analysis, there was no excess of vulva cancer in younger Indigenous women. Improvement in the accuracy of Indigenous status data is required not only in the four low-identification registries, but also in the four high-identification registries to a lesser extent.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis of vulvar cancer cases diagnosed in the Northern Territory found that the age adjusted incidence of vulvar cancer among Indigenous women aged 0 to 49 years living in remote communities in the East Arnhem district on the north coast of the Northern Territory was 31.1 per 100 000 (95% CI: 13.1-49.1), over 50 times higher than the national Australian rate for the same age group. 34 Possible causes for this high incidence are unclear, but possibilities include a very high prevalence of oncogenic HPV genotypes, presence of a highly virulent variant of an oncogenic HPV genotype, genetic susceptibility to another cause of vulvar cancer, high prevalence of immunosuppressive conditions such as diabetes or HIV, a very high prevalence of smoking; or a combination of these factors. 34 …”
Section: Vulval Cancermentioning
confidence: 99%
“…34 Possible causes for this high incidence are unclear, but possibilities include a very high prevalence of oncogenic HPV genotypes, presence of a highly virulent variant of an oncogenic HPV genotype, genetic susceptibility to another cause of vulvar cancer, high prevalence of immunosuppressive conditions such as diabetes or HIV, a very high prevalence of smoking; or a combination of these factors. 34 …”
Section: Vulval Cancermentioning
confidence: 99%
“…With regards to the topic of this article, research conducted by Condon et al (2009) found that the ageadjusted incidence rate for vulvar cancer for the Indigenous women in East Arnhem Land ages 0-49 is 31.1 per 100,000, more than 50 times higher than the national Australian average for the same age group. Research findings from the qualitative study discussed in the present article indicate that there is acute psychosocial distress associated with vulvar cancer for the Indigenous women in East Arnhem Land affected by this condition Rawson 2013a, 2013b).…”
Section: Introductionmentioning
confidence: 95%
“…The findings are from a major study funded by the National Health and Medical Research Council of Australia (NHMRC) (Condon et al 2011(Condon et al -2012) that incorporated two projects, one focusing on the psychosocial and the other on the genetic factors associated with a vulvar cancer cluster (Condon et al 2009) of Indigenous women in East Arnhem Land. Specifically, the bioethical issues presented in this article come from the qualitative research component of the psychosocial study that explored community beliefs about possible causation of the cluster and aspects of the cancer experience for the women affected.…”
Section: Introductionmentioning
confidence: 99%